PATOGENITAS ISOLAT BAKTERI ASAM LAKTAT DARI USUS IKAN REPANG (Puntioplites waandersi) TERHADAP IKAN NILA (Oreochromis niloticus) - Andriani, Puput; Agustina, Agustina; Saptiani, Gina (JARI : Jurnal Akuakultur Rawa Indonesia, 2023)
This study aims to determine the pathogenicity of lactic acid bacteria from repang fish on clinical symptoms, anatomical pathology, hematology and survival rate of tilapia. This study used a completely randomized design with 5 treatments and 3 replications, namely Phosphate Bufferet Saline (PBS) 0.1 ml/fish as a negative control, A. hydrophila 106 CFU/ml as a negative control, Enterococcus sp. 106 CFU/ml, Lactobacillus sp. 106 CFU/ml and Lactococcus sp. 106 CFU/ml, fish given intramuscularly. Parameters observed included clinical symptoms, anatomical pathology. Hematology and survival. Tilapia with an average weight of 30 g/fish were reared for 7 days in an aquarium measuring 50×40×30 cm3 with a volume of 40 L of water, at a density of 10 fish/aquarium. Fish are fed 3 times a day. Administration of lactic acid bacteria Lactobacillus sp. showed the highest survival compared to the treatment with other isolates. Hematological parameters were in the normal range in all treatments except for the treatment with A. hydrophila bacteria. Changes in clinical symptoms of tilapia treated with injection with A. hydrophila showed clinical symptoms of swimming patterns, decreased appetite and also moved more hyperactively. In fish treated with Enterococcus sp., Lactococcus sp., and Lactobacillus sp. generally shows normal condition. Anatomical changes in fish treated with A. hydrophila bacteria showed changes in the form of excess mucus, redness on the back, pale body and easily detached scales. The three lactic acid bacteria from the intestines of repang fish are safe for tilapia and can be used in further probiotic tests.